1975
DOI: 10.1149/1.2134377
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemichromic Systems for Display Applications

Abstract: Several electrochemical systems exhibit an intense color change when an electrochemical reaction is induced by an applied electrical field or current. The electrochemical and electro‐optical properties of several such systems have been investigated. These systems are termed electrochemichromic and they can be classified into the following categories: (i) simple redox reaction; (ii) redox reaction coupled with an independent chemical reaction, resulting in variable color persistence; (iii) redox reaction couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(38 citation statements)
references
References 12 publications
1
36
0
1
Order By: Relevance
“…Uma segunda reação entre X -e o íon radical V + pode ocorrer imediatamente se o solvente usado é a água, o qual resulta em um sólido púrpura insolúvel (VX) que precipita como um filme sobre a superfície do cátodo: 77 , por sua vez, trata-se de um composto contendo nitrogênio que forma precipitados coloridos com ânions, quando no estado catiônico monovalente. Sob oxidação, ela pode tornar-se branca ou com uma coloração avermelhada.…”
Section: Materiais Eletrocrômicos Catódicosunclassified
“…Uma segunda reação entre X -e o íon radical V + pode ocorrer imediatamente se o solvente usado é a água, o qual resulta em um sólido púrpura insolúvel (VX) que precipita como um filme sobre a superfície do cátodo: 77 , por sua vez, trata-se de um composto contendo nitrogênio que forma precipitados coloridos com ânions, quando no estado catiônico monovalente. Sob oxidação, ela pode tornar-se branca ou com uma coloração avermelhada.…”
Section: Materiais Eletrocrômicos Catódicosunclassified
“…A large number of organic compounds develop absorption bands in the visible region of the spectrum upon redox reaction and most compounds in this class exhibit electrochromic phenomena by reversible electrode deposition, e.g. viologens [1e4], pyridines [5], ortho-toluidines [6], and anthraquinones [7]. The colouration is achieved by an oxidatione reduction reaction, which can be a simple redox reaction or a redox reaction coupled with a chemical reaction to produce an insoluble coloured species.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen is the simplest impurity in semiconductor materials, and the presence of hydrogen changes the electrical and the optical properties of the compound semiconductor materials drastically. Especially the studies of hydrogen in metal oxides have been reported for various applications, [1][2][3][4][5] but hydrogen in metal nitrides has not been studied so much. As well as hydrogen in metal oxides, hydrogen in metal nitrides is very important when high quality p-type GaN thin films were prepared because hydrogen in p-type GaN plays a role of passivator against acceptor Mg. 6) Therefore it is so valuable to make the relationship clear between hydrogen and defects or impurities in the metal nitride thin films.…”
Section: Introductionmentioning
confidence: 99%